TUBE MORPHOLOGY AND STRUCTURE OF THE BATHYAL MEDITERRANEAN SERPULID HYALOPOMATUS VARIORUGOSUS BEN-ELIAHU & FIEGE, 1996 (ANNELIDA, POLYCHAETA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
The species studied differs from the other Hyalopomatus species by having a peculiar rugose sculptured outer tube surface. This character is markedly variable; it can be more or less developed and may also vary along the same tube. Observed by SEM, this rugosity proves to consist of irregular flaps, roughly following the growth lines. SEM observations on transverse fractures show a homogeneous composition of the tube wall, consisting of calcium carbonate crystals. These crystals show a prismatic habitus and are arranged in a homogeneous granular microcrystalline structure. New records of H. variorugosus are from deep water stations in the Western Mediterranean and from Pleistocene bathyal deposits of Southern Italy. The discussion covers aspects of tube characters of use for taxonomy.